Investigating The Entrepreneurial Self-Efficacy in the Relationship between Entrepreneurship Education and Student’s Self-Employment Intentions: An Empirical Analysis from Malaysia - Asmaul Husna, Haris Fadzilah; Mohammad Naim, Ismail; Mohammad Mujaheed, Hassan; Muhamad Hafiz, Hassan; Mohammad, Abdullah (Center for Research and Technological Development and Engineering of URBE (CIDETIU), 2024)
The rise of self-employment is influenced by a number of personal and environmental factors among which we may distinguish the factors linked to education in entrepreneurship as well as personal characteristics. Given this aspect, the purpose of this paper is to investigate the main factors influencing students’ self-employment intentions, paying particular attention to their entrepreneurial self-efficacy. Additionally, the paper aims to explore the effect of entrepreneurial self-efficacy on the relationship between entrepreneurship education and self employment intention. We conducted a study where results were based on the outcomes of a survey among Malaysian public university students (N = 388). Our four main hypotheses were tested through multiple regression analysis. The findings highlighted that the students with an entrepreneurial self-efficacy reported a positive relationship with self-employment intention. The variables that positively influenced the self-employment intentions of the students were entrepreneurial self-efficacy and entrepreneurship education. Furthermore, this entrepreneurial self- efficacy positively mediates the relationship between entrepreneurship education and self-employment intention. For this reason, emphasis should be placed on both formal and informal entrepreneurial education, which will increase the propensity of young people to choose an entrepreneurial career. Keywords: Self-Employment Intentions Entrepreneurship Education Entrepreneurial SelfEfficacy Students.